Impact of aging on obstetric outcomes: defining advanced maternal age in Barcelona - Marta Claramonte Nieto; Eva Meler Barrabes; Sandra Garcia Martínez; Mireia Gutiérrez Prat; Bernat Serra Zantop (BMC, 2019)
Abstract Background Women of advanced maternal age (AMA) are a growing population, with higher obstetric risks. The Mediterranean population has specific characteristics different from other areas. Thus, the objective of this study was to establish a cut-off to define AMA in a selected mediterranean population coming from a tertiary referral private/mutual health hospital in Barcelona. Methods Retrospective cohort of euploid singleton pregnancies delivered from January 2007 to June 2017. Main maternal outcomes were: gestational diabetes, preeclampsia, placenta previa, c-section and prolonged hospitalization (≥ 7 days). Main adverse perinatal outcomes were: stillbirth, prematurity, preterm prelabor rupture of membranes, low birth weight, need of admission at a neonatal intensive care unit and perinatal mortality. Adjustment for confounding factors (smoking, previous comorbilities, parity, assisted reproductive techniques (ART) and obesity) was performed. Results A total of 25054 pregnancies were included. Mean maternal age was 34.7 ± 4.2 years, with 2807 patients in the group of age between 40 and 44 years (11.2%) and 280 patients ≥45 years (1.1%). Women at AMA had higher incidence of previous comorbilities (compared to the reference group of women < 30 years): prior c-section, chronic hypertension and obesity. In addition, they were more likely to use ART. After adjusting for confounding factors, maternal age was an independent and statistically significant risk factor for gestational diabetes (OR 1.66/2.80/3.14) for ages 30-39, 40-44 and ≥ 45 years respectively, c-section (OR 1.28/2.41/7.27) and placenta previa (OR 2.56/4.83) for ages 40-44 and ≥ 45 years respectively, but not for preeclampsia (neither early-onset nor late-onset). Risk of emergency c-section was only increased in women ≥45 years (OR, 2.03 (95% CI, 1.50-2.74). In the other groups of age, the increase in c-section rate was because of elective indications. Age ≥ 45 years was associated with iatrogenic prematurity < 37 weeks (OR 2.62, 95% CI 1.30-5.27). No other relevant associations between AMA and maternal or neonatal outcomes were found. Conclusions Maternal age is an independent risk factor for adverse obstetric outcomes. Age ≥ 40 years was associated to relevant increased risks and reveals to be an adequate cut-off to define AMA in our population.